AN INNOVATIVE APPROACH TO THE DEVELOPMENT OF STUDENTS' PROFESSIONAL COMPETENCIES IN ENGLISH LESSONS - Dildora Jabborova,, Dildora Jabborova, (Журнал иностранных языков и лингвистики, 2021)
The article discusses the importance of innovative technologies in teaching students career-oriented communication in English language teaching. Examples of tasks used in the formation of professional speech of future specialists are given.